TANGGUNG JAWAB JASA ANGKUTAN UDARA TERHADAP KECELAKAAN PESAWAT MELALUI PENELITIAN DI PT GAPURA ANGKASA DENPASAR - Dian Putri Yuliana, Ida Ayu; Sukranatha, A. A. Ketut (Kertha Semaya : Journal Ilmu Hukum, 2014)
Responsibility of air transport services to the plane crash, was written with the aim to know and understand more about the responsibilities of the air carrier in a plane crash. In this research uses empirical legal research, which is where the writing refers to the approach to the empirical aspects of the research and books / materials laws. The conclusion of this paper is to a large indemnity to be paid based on the losses suffered by the passengers. Compensation filing requirements must be included with the related documents as well as a certificate from the authorities.
Keywords: Responsibility, Air Freight, Indemnity